Involvement of Proteasome and Macrophages M2 in the Protection Afforded by Telmisartan against the Acute Myocardial Infarction in Zucker Diabetic Fatty Rats with Metabolic Syndrome - C. Di Filippo; C. Rossi; B. Ferraro; R. Maisto; A. De Angelis; F. Ferraraccio; A. Rotondo; M. D'Amico (Hindawi Limited, 2014)
This study investigated the involvement of proteasome and macrophages M2 in the protection afforded by telmisartan against the acute myocardial infarction in Zucker diabetic fatty (ZDF) rats with metabolic syndrome. ZDF rats were treated for three weeks with telmisartan at doses of 7 and 12 mg/kg/day. After treatment, rats were subjected to a 25 min occlusion of the left descending coronary artery followed by 2 h reperfusion (I/R). At the end of the I/R period, biochemical, immunohistochemical, and echocardiographic evaluations were done. Telmisartan treatment (7 mg/kg and 12 mg/kg) reduced the myocardial infarct size, the expression of proteasome subunits 20S and 26S, and the protein ubiquitin within the heart. The compound has led to an increased M2 macrophage phenotype within the cardiac specimens and a modification of the cardiac cytokine and chemokine profile. This was functionally translated in improved cardiac performance as evidenced by echography after 2 h reperfusion. 7 mg/kg/day telmisartan was sufficient to improve the left ventricular ejection fraction LVEF of the rat heart recorded after I/R (e.g., vehicle 38 ± 2.2%; telmisartan 54 ± 2.7%) and was sufficient to improve the diastolic function and the myocardial performance index up to values of 0.6 ± 0.01 measured after I/R.